Prevalence and Socio-Demographic Characteristics of Threatened Abortion among Women: Experience of 100 Cases in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Threatened abortion is very crucial condition among the pregnant women.Objective: The purpose of the present study was to assess the prevalence and socio-demographic characteristics of threatened abortion.Methodology: This cross-sectional study was done in the Department of Obstetrics & Gynaecology at Rajshahi Medical College Hospital, Rajshahi, Bangladesh from January 2004 to December 2004 for a period of one year. Patients admitted with the history of pregnancy with per vaginal bleeding before 20 weeks without having any cervical effacement or dilatation were included in this study group. Socioeconomic status of the patients was reflected by their places of habitations, educational back ground, occupations, and level of income.Results: The threatened abortion was reported at all stage of reproductive age. Women between 20 to 30 years had constituted the largest age group (58.0%). About 80.0% of the patients were illiterate. Of the 100 patients, 58 lived in rural areas or urban slums and 81 in kucha floored houses or slums. A large majority (77 out of 100) belonged to low or very low-income groups. Most of the study population were coming from low-income group (10,000.00 to 20,000 BDT) which was 63.0% cases followed by middle Income (20,000.00 to 50,000 BDT) and very low Income (less than 10,000.00 BDT) were in 22.0% cases and 14.0% cases respectively.Conclusion: In conclusion middle age illiterate women are the most commonly suffering from threatened abortion.Journal of National Institute of Neurosciences Bangladesh, July 2024;10(2):114-118